(untitled) (E Conference Zone, 2022)
The article presents the essence of the digestive processes in the anterior stomachs and the etiology of disturbances of these processes in productive cows, the dominant role of these disorders in metabolism, as well as a brief summary of laboratory studies of the rumen, as one of the methods for diagnosing diseases of the anterior angina and analysis of preliminary studies in this direction